EDUCATIONAL ROBOTS IN THE FUNCTION OF DEVELOPING ALGORITHMIC THINKING OF PRESCHOOL CHILDREN - Matović, Sofija; Ristić, Miroslava (Metodička teorija i praksa, 2024)
In the modern world, children are growing up surrounded by digital technologies which are used spontaneously and intuitively. It is necessary to choose an appropriate methodological approach that supports interdisciplinary and cooperative work directed towards problem-solving and the development of children's creativity in order to create conducive conditions for the well-being of children in an educational environment supported by technology. This paper aims to construct a methodical model for the effective implementation of educational robots to develop algorithmic thinking in preschool children. The research is based on theoretical foundations, with arguments drawn from practice. Analytical-deductive and hypothetical-deductive methods were applied, as well as the method of modeling, through which was developed an innovative methodical approach (five-step model), based on research conducted for an unpublished master's thesis (Matović, 2022). The results indicate that the five-step model can contribute to the effective implementation of educational robots in educational work, encourage algorithmic thinking, interdisciplinary skills, and the development of competencies significant for lifelong learning (communication, self-reflection, planning).
Keywords: educational robots; algorithmic thinking; child; preschool teacher; competences